Interactive Curve Modeling With Applications to Computer Graphics, Vision and Image Processing - Sarfraz, Muhammad (Springer London : Imprint: Springer, 2008)
Interactive curve modeling techniques and their applications are extremely useful in a number of academic and industrial settings, and specifically play a significant role in multidisciplinary problem solving, such as in font design, designing objects, CAD/CAM, medical operations, scientific data visualization, virtual reality, character recognition, and object recognition, etc. Various problems such as iris, fingerprint, and signature recognition, can also be intelligently solved and automated using curve techniques. This broad-ranging textbook covers curve modeling with solutions to real life problems relating to computer graphics, vision, image processing, geometric modeling and CAD/CAM. Well-explained, easy-to-understand chapters deal with basic concepts, curve design techniques and their use to various applications, and a wide range of problems with their automated solutions via computers. Features and topics: • Provides a class of practical solutions to real life and multidisciplinary problems • Offers students supporting pedagogical tools in the form of a thorough introductory chapter, individual chapter introductions and end summaries, as well as end-of-chapter exercises • Presents both classical and up-to-date theory, with practice to get problems solved in diverse disciplines • Focuses on interdisciplinary methods and up-to-date methodologies in the field • Imparts a description and analysis of a variety of classes of splines for use in CAGD (computer-aided geometric design), CAD (computer-aided design), CAE (computer-aided engineering), computer graphics, computer vision, image processing and other disciplines • Aims to stimulate views and provide a source where readers can find the latest state-of-the-art developments in the field, including a variety of techniques, applications, and systems necessary for solving problems Interactive Curve Modeling also will serve as an important tool for readers; as an extremely useful textbook for senior undergraduates as well as graduate students in the areas of computer science, engineering, and other computational sciences. This comprehensive text can equally act as an invaluable resource for those practitioners and researchers looking for an introduction to the state-of-the-art on the topic. Professor Sarfraz has many years of experience researching and teaching in the field, winning an award for Excellence in Research at the King Fahd University of Petroleum and Minerals, Saudi Arabia.